2023
DOI: 10.3390/ijms241713133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bruton’s Tyrosine Kinase (BTK) on Epithelial–Mesenchymal Transition (EMT) Processes and Cancer Stem Cell (CSC) Enrichment in Head and Neck Squamous Cell Carcinoma (HNSCC)

Franziska Leichtle,
Annika C. Betzler,
Carlotta Eizenberger
et al.

Abstract: Constitutively active kinases play a crucial role in carcinogenesis, and their inhibition is a common target for molecular tumor therapy. We recently discovered the expression of two oncogenic isoforms of Bruton’s Tyrosine Kinase (BTK) in head and neck squamous cell carcinoma (HNSCC), Btk-p80 and BTK-p65. However, the precise role of BTK in HNSCC remains unclear. Analyses of a tissue microarray containing benign and malignant as well as inflammatory tissue samples of the head and neck region revealed the prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…ATP8B3 (belongs to P4-ATPases) is a subfamily member of P-type ATPases that flip phospholipids across membranes to generate lipid asymmetry, which participate in cell component composition [ 42 ]. BTK encodes Bruton’s Tyrosine Kinase and plays an oncogenic role on head and neck squamous cell carcinoma, promoting epithelial–mesenchymal transition processes and cancer stem cell enrichment [ 43 ]. Research have indicated that Inhibitors targeted to BTK have been developed for hematological tumors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATP8B3 (belongs to P4-ATPases) is a subfamily member of P-type ATPases that flip phospholipids across membranes to generate lipid asymmetry, which participate in cell component composition [ 42 ]. BTK encodes Bruton’s Tyrosine Kinase and plays an oncogenic role on head and neck squamous cell carcinoma, promoting epithelial–mesenchymal transition processes and cancer stem cell enrichment [ 43 ]. Research have indicated that Inhibitors targeted to BTK have been developed for hematological tumors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%